Degradation behavior and osseointegration of Mg–Zn–Ca screws in different bone regions of growing sheep: a pilot study. (18th October 2022) - Marek, Romy; Ćwieka, Hanna; Donohue, Nicholas; Holweg, Patrick; Moosmann, Julian; Beckmann, Felix; Brcic, Iva; Schwarze, Uwe Yacine; Iskhakova, Kamila; Chaabane, Marwa; Sefa, Sandra; Zeller-Plumhoff, Berit; et al.
Abstract: Magnesium (Mg)-based implants are highly attractive for the orthopedic field and may replace titanium (Ti) as support for fracture healing. To determine the implant–bone interaction in different bony regions, we implanted Mg-based alloy ZX00 (Mg < 0.5 Zn < 0.5 Ca, in wt%) and Ti-screws into the distal epiphysis and distal metaphysis of sheep tibiae. The implant degradation and osseointegration were assessed in vivo and ex vivo after 4, 6 and 12 weeks, using a combination of clinical computed tomography, medium-resolution micro computed tomography (µCT) and high-resolution synchrotron radiation µCT (SRµCT). Implant volume loss, gas formation and bone growth were evaluated for both implantation sites and each bone region independently. Additionally, histological analysis of bone growth was performed on embedded hard-tissue samples. We demonstrate that in all cases, the degradation rate of ZX00-implants ranges between 0.23 and 0.75 mm/year. The highest degradation rates were found in the epiphysis. Bone-to-implant contact varied between the time points and bone types for both materials. Mostly, bone-volume-to-total-volume was higher around Ti-implants. However, we found an increased cortical thickness around the ZX00-screws when compared with the Ti-screws. Our results showed the suitability of ZX00-screws for implantation into the distal meta- and epiphysis. Graphical Abstract: